Tingkat Pengetahuan Pembelajaran Atletik Lari Jarak Pendek Pada Siswa Sekolah Menengah Atas Kelas XII - Cika Sinta Anggraeni; Rhama Nurwansyah; Aria Kusuma Yuda R (Peneliti.net, 2021)
The problem in this research is how big the level of knowledge in learning short distance running athletics class XII at SMA Negeri 5 Karawang. The purpose of this study was to determine the level of knowledge in learning short distance running athletics class X at SMA Negeri 5 Karawang. The subjects in this study were all students of class XII. The data collection technique used in this research is descriptive research. The data collection technique used a questionnaire questionnaire. This research questionnaire has a reliability of 0.812. The population in this study was class XII students at SMA Negeri 5 Karawang with a sample of 108 students. The instrument used is in the form of a questionnaire/questionnaire using Gform. The data analysis technique used descriptive quantitative and percentage analysis. The results of this study indicate that the level of knowledge of students about learning athletic distance running in class XII at SMA Negeri 5 Karawang is with a percentage of (1.9%) 2 students in the Very Low category, as many as (26.9%) 29 students in the Low category, as many as (53.7%) 58 students in the Medium category, as many as (8.3%) 9 students in the High category, and as many as (9.3%) 10 students in the Very High category.